The pursuit of methodological harmonization within the holistic sustainability assessment of CCU projects: A history and critical review - Newman, Alex J. K.; Styring, Peter (Frontiers in Sustainability, 2023)
Environmental sustainability assessments have been conducted around consumer goods since the 1960’s, these adopted comparative approaches and followed no accepted methodology. As sustainability assessment rose to prominence, methodological standardisation was universally called for. Furthermore, two additional ‘strands’ of sustainability emerged, economic and societal; forming what has recently been termed the ‘triple helix’. Efforts have been made across the CCU (carbon capture and utilisation) community to align, or ‘harmonise’, the respective assessment formats. Ultimately, targeting enhanced understanding of the interconnections and trade-offs between the three strands, and communication of findings to both industry and policymakers. This review examines key methodologies presented in the field. These were collated through targeted literature searches, focussing on standalone, CCU specific, and harmonised methodologies. Relevant guidance originates with ISO’s 2007 standards and terminates in McCord et al.’s 2021 ‘triple helix framework’. Other key works reviewed include UNEP / SETAC’s S-LCA (social life cycle assessment) guidelines, and GCIs (Global CO2 Initiative) integrated LCA and TEA (techno-economic assessment) guidelines. Analysis of the identified methodologies first considers each assessment strand in isolation, subsequently evaluating efforts towards their CDU specific harmonisation and integration. Using the collated primary and secondary literature, a taxonomy of assessment methodologies leading to the triple helix framework is produced. Key methodological difficulties and divergent schools of thought are discussed, notably the prescription of system boundaries, impact indicators, and characterisation methods. The overarching conclusion of the review is that while a robust combined LCA and TEA assessment methodology has been attained, holistic approaches incorporating social sustainability are still lacking; with substantial problems remaining unsolved. A majority of these originate from SIA’s immaturity relative to LCA and TEA, causing issues around data availability and handling methods; exacerbated by the presence of qualitative data. Until a greater degree of maturity is achieved, SIA should be utilised within holistic assessments as a screening tool, determining the suitability of a process or system for more granular assessment.